Applications’ Job Pursuit Intentions and Social Networking Sites: An Exploratory Study among Vietnamese Students - Nguyen, Vu Minh An (2014)
Research purpose: A growing trend of using social networking or social media in employment market for professional purpose has received much attention from academic scholars. It then became a topical subject that motivated human resource (HR) professionals to do research on. Many studies have been published to demonstrate social networking sites (SNS) as an emergent recruiter tool in the last few years. However, most of them focused on the recruiters or employers’ point of view and ignored the important role of job seekers in this practice. In other words, there has been very few research probing applicants’ reactions or behaviors towards the employer’ use of SNS in recruitment and selection procedures. In attempt to fill this gap, the purpose of the present paper is to find out how applicants perceive this emerging HR trend, revealing new theoretical and empirical insights. In particular, the study is about to obtain a better understanding on the influence of the main elements of social recruitment practice including perceived process fairness, corporate reputation, information qualities and qualities of SNS on students’ job pursuit intentions. Design/methodology/approach: To achieve research objectives, quantitative approach with electronic questionnaires is used as the main data collection tool. This approach is expected to provide reliable and valid results in order to test hypotheses deriving from the theoretical background. Out of 500 questionnaires have been sent, 232 were completed and returned but only 180 were used because 52 invalid ones were removed. Then, SPSS software was adopted to obtain the descriptive analysis and PLS estimation software was applied to examine relationships among constructs. Findings: An empirical study using Partial Least Squares path modeling has revealed that perceived process fairness, information qualities of social networking sites have positive effects on job pursuit intentions towards the employer’s use of SNS recruitment and selection procedures. Meanwhile, corporate reputation has no significant relationship with intentions to apply and accept job offer among applicants Originality/value: This is the first paper providing a conceptual framework to test whether the use of SNS by employers will positively or adversely influence students’ job pursuit intentions in the context of Vietnam. It also contributes to the academic field by developing new insights into the applicants’ perceptions of a particular web-based recruitment and selection setting.